THE INCREASING THE INTRODUCTION OF BALANCED NUTRITIOUS FOOD THROUGH COOKING CLASS ACTIVITY ON CHILDREN OF 3-4 YEARS OLD AT PPT PELANGI KECAMATAN PAKAL SURABAYA - Abdul Muhith Muhith; Maya Zainiyah (Bina Sehat Press. Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2021)
The research purpose is to increase the introduction of balanced nutritions food. The research method used was Classroom Action Research (CAR). The researcher subjects were 22 children of 3-4-year-old children at PPT Pelangi, Pakal, Surabaya. Data collection techniques included: planning, implementation, observation, and reflection. This research consisted of pre-cycle, cycle I and cycle II with 2 meetings/ cycle. The research result showed that in the pre-cycle, it obtained 46,6 %, there was An increase in the first cycle of 61,4 %, it showed an increase in the number of children who developed well, although it was not maximally yet, in the second cycle, It increased as 83 % it showed an increase in the percentage of development with very good growth.